Exercise and Adipose Tissue Macrophages: New Frontiers in Obesity Research? - Goh, Jorming; Goh, Kian Peng; Abbasi, Asghar (Frontiers in Endocrinology, 2016)
Obesity is a major public health problem in the 21st century. Mutations in genes that regulate substrate metabolism, subsequent dysfunction in their protein products, as well as other factors such as increased adipose tissue inflammation, are some underlying etiologies of this disease. Increased inflammation in the adipose tissue microenvironment is partly mediated by the presence of cells from the innate and adaptive immune system. A subset of the innate immune population in adipose tissue include macrophages, termed adipose tissue macrophages (ATMs), which are central players in adipose tissue inflammation. Being extremely plastic, their responses to diverse molecular signals in the microenvironment dictate their identity and functional properties, where they become either pro-inflammatory (M1) or anti-inflammatory (M2). Endurance exercise training exerts global anti-inflammatory responses in multiple organs, including skeletal muscle, liver and adipose tissue. The purpose of this review is to discuss the different mechanisms that drive ATM-mediated inflammation in obesity and present current evidence of how exercise training, specifically endurance exercise training, modulates the polarization of ATMs from an M1 to an M2 anti-inflammatory phenotype.